H HUBUNGAN ANTARA KLASIFIKASI STROKE DENGAN GANGGUAN FUNGSI MOTORIK PADA PASIEN STROKE - Zaqyyah Huzaifah; Dody Dody (LPPM Universitas Sari Mulia, 2021)
Background: Stroke is a disorder of brain function that arises suddenly due to disruption of cerebral blood circulation. Stroke is the second leading cause of death in the world and stroke is divided into 2, namely hemorrhagic stroke and non-hemorrhagic stroke. Motor disorders that commonly occur in stroke patients are hemiplegia and hemiparesis. Objective: This study aims to determine whether there is a relationship between stroke classification and motor function disorders in stroke patients. Method: The design of this study used a cross sectional design with a sample of 36 respondents. Conclusion: Correlation analysis using chi square test with = 0.05 with the result that there is a relationship between stroke classification and motor function disorders in stroke patientswith p value: 0.000.